On the Investigation and Handling Rules of Fishery Administrative Law Enforcement Cases - Liu, Xvwei; Xing, Zheng (International Journal of Social Sciences and Public Administration, 2024)
Fishery administrative law enforcement plays a crucial role in fishery management, aiming to maintain the sustainable utilization of fishery resources and ecological balance. The purpose of this paper is to explore the investigation and handling rules of fishery administrative law enforcement cases, and analyze their importance and challenges in practical operation.